The Oxford handbook of the Indian economy in the 21st century: understanding the inherent dynamism - Goyal, Ashima (Oxford Univ. Press, 2014)
Structure and reform -- The macroeconomy -- The open economy -- Inclusion: equality and opportunity -- Governance -- Infrastructure -- Sectors -- Factors: technology, labour, finance